Gender differences in reward-based crowdfunding - Lin, Tse-Chun; Pursiainen, Vesa (Journal of Financial Intermediation, 2023)
We document several gender differences in reward-based crowdfunding by analyzing a large sample of Kickstarter campaigns. We argue that these differences are most plausibly explained by male entrepreneurs’ relative over-optimism. Suggesting a tendency to overestimate the demand for their products, we find that male entrepreneurs set higher goal amounts, resulting in more frequent campaign failures. In successive campaigns, male entrepreneurs’ goal amounts and success rates converge toward those of female entrepreneurs, consistent with entrepreneurial experience mitigating the behavioral bias. Our findings suggest that entrepreneurs learn from experience, and that female first-time entrepreneurs may have more realistic expectations of the demand for their products, increasing their success rates in crowdfunding. Moreover, although serial entrepreneurs exhibit better performance already in their first campaigns, they still improve over successive campaigns, further highlighting the importance of entrepreneurial learning.